POTENCY OF CONSORTIUM SYMBIONT MICROBE OF MANGROVE LITTER AS NATURAL PRESERVATIVE FOR TOFU (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Symbiont bacteria from mangrove litter are known to have antimicrobial activity against Staphylococcus aureus. However, only a handful of research has been carried out on microbes as an innovative natural material for preserving food, especially tofu. This research used four species of mangrove litter symbiont microbe, which were cultured as a microbial consortium. The study aimed to determine the potential of consortium microbe as tofu preservatives. The tofu was soaked in the liquid culture of the consortium microbe as a treatment, while for the positive control, it was immersed in tofu using 37% formalin, and for the negative control, the tofu was not given any treatment. The organoleptic observations on the second day showed that the tofu with all treatment did not change in odor, color, and texture. On the other hand, tofu without treatment became more acidic in odor, with a yellowish color, and showed a softer texture. On the third day, tofu with bacterial microbe treatment had a slight change in odor, the color became yellowish, and the texture was slightly softened. Tofu with formalin treatment did not change in color, but became more solid and extruded formalin odor. Tofu with the consortium microbe immersion treatment had the least amount (6.795x103) of total microbe count, compared with the formalin treatment (9.766x103) and without treatment (9.766x103).